Analisis faktor-faktor yang mempengaruhi Transparansi Informasi keuangan Via Website (Studi empiris keuangan pada pemerintah daerah di Jawa Timur periode 2018) - Adni Dwi Astuti (Universitas Muhammadiyah Kendari, 2020)
One of the responsibility of local government to the community is to provide a report of liability, one of which is the financial statement. Transparency is one aspect that illustrates that institution has made a good obligation. Some of the variables used in this study were the financial statements of the East Java local government. This research uses quantitative methods with secondary data taken from the official website of the local government of East Java and BPS Jawa Timur. Research samples amounted to 38 districts/cities in East Java. The analysis used is a simple linear regression. The results of the study explained that in partial variables the population, regional expenditure and indigenous revenue have an unpositive influence on the transparency of financial information via the website of the East Java government.